The Impact of Interactive Acting Learning as an Alternative to Digital Acting Teaching in Malaysian Art School: A Comprehensive Review - Muhammad Faisal Ahmad, Muchammad Bayu Tejo Sampurno, Mardiana Ismail, Nor Shuradi Haji Nor Hashim (Tanjung Malim, 2024)
The Impact of Interactive Acting Learning as an Alternative to Digital Acting Teaching in Malaysian Art School: A Comprehensive Review by Muhammad Faisal Ahmad, Muchammad Bayu Tejo Sampurno, Mardiana Ismail, Nor Shuradi Haji Nor Hashim